2022
DOI: 10.3346/jkms.2022.37.e30
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Atopic Dermatitis in Korean School-Aged Children and Adolescents According to Onset Age and Severity

Abstract: Background Atopic dermatitis (AD) is a heterogeneous disease with different age of onset, disease course, clinical symptoms, severity, and risk of comorbidity. The characteristics of children with AD also vary by age or country. However, little is known about the clinical characteristics of AD in Korean school-aged children and adolescents. Furthermore, there are few studies on phenotypic differences according to onset age. This study aimed to explore the clinical characteristics and phenotypes ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…These findings agree with similar reports, showing eczema onset before 2 years of age to be associated with development of FA, asthma and hay fever. [20][21][22] Onset of eczema in the first 2 months has even been reported to have the strongest association with development of FA by age 3. 23 Taken together, our findings suggest that individuals with disease onset before 6 months and persistent eczema are at highest risk for developing allergic multimorbidity during childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings agree with similar reports, showing eczema onset before 2 years of age to be associated with development of FA, asthma and hay fever. [20][21][22] Onset of eczema in the first 2 months has even been reported to have the strongest association with development of FA by age 3. 23 Taken together, our findings suggest that individuals with disease onset before 6 months and persistent eczema are at highest risk for developing allergic multimorbidity during childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Future investigations concerned with the effect of early-life eczema on allergic multimorbidity should consider the integration of disease severity for eczema, food allergies, asthma and hay fever, since it was repeatedly shown that eczema severity was associated with the development and severity of other allergic diseases. 13,18,21,40 Further, there seems to be a heterogenic association between eczema phenotypes and different allergenic foods. 22 This distinction could result in a more detailed understanding of the allergen specific associations present among comorbid allergic diseases, if applied to future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical AD phenotypes according to age at onset can be clearly defined. Generally, 4 types are classified: infantile (<2 years), early childhood (2–6 years), late childhood (6–12 years), and adolescence (12–18 years) [ 33 , 34 ].…”
Section: Subtypesmentioning
confidence: 99%
“…A European birth cohort study revealed that the prevalence of asthma and FA by 6 years of age strongly increased among children with early phenotypes (aged <2 years), especially those with persistent symptoms [ 35 ]. Similarly, a recent Korean study of school-aged children and adolescents with AD found that comorbid FA, allergic rhinitis, and asthma as well as inhalant allergen sensitization were more prevalent in infancy-onset (<2 years of age) than childhood-onset AD (≥2 years of age) [ 34 ]. While a significant proportion of patients with the early-onset phenotype can reach complete remission before 2 years of age, another proportion, estimated at up to 40%, continues to suffer from the disease over a long period of time [ 11 ], and this category of patients may be at high risk for atopic march [ 36 ].…”
Section: Subtypesmentioning
confidence: 99%
“…Patient clinical history and examination are the first steps toward a diagnosis of kiwifruit allergy [34]. Other clinical diagnostic tools include skin prick test (SPT), enzymelinked immunosorbent assay (ELISA), component-resolved diagnosis (CRD), and doubleblind placebo-controlled food challenge (DBPCFC) [35]. DBPCFC is considered to be the gold standard test to detect a food allergy because it ensures an objective assessment of outcomes without operator-specific preconceptions or biases [36].…”
Section: Diagnosismentioning
confidence: 99%